Creating a healthy organization: changing role of a successful education leader - Ayodele, Lasisi Abass; Mohd Ali, Hairuddin (Penerbit UPSI, 2012)
People in an organization are critical to direct, but healthy organization is very important to improve productivity, quality, and performance, one should involve the people who do the work. This study focuses on leadership with the aims of exploring the roles of education institutional leader in creating a healthy organization for quality achievement. It emphasizes the necessary roles of successful leader in organization through implementations of major component which suggested as necessary and responsible for achieving a healthy organization. The literatures on leadership were consulted for paper justification. This study based its findings on former researcher’s factors that responsible for healthy organization and creates a model for clear procedure in creating a healthy organization. Similarly, this study employed descriptive statistical method with Factor Analysis to describe the results of the findings. Nevertheless, the findings from this study were useful for administrators as well as other staff for a healthy organization achievement